1998
DOI: 10.1002/(sici)1097-0282(199809)46:3<155::aid-bip3>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Studies of conformational isomerism in α-melanocyte stimulating hormone by design of cyclic analogues

Abstract: Results of energy calculations for α‐MSH (α‐melanocyte stimulating hormone, Ac‐Ser1‐Tyr2‐Ser3‐Met4‐Glu5‐His6‐Phe7‐Arg8‐Trp9‐Gly10‐Lys11‐Pro12‐Val13‐NH2) and [D‐Phe7]α‐MSH were used for design of cyclic peptides with the general aim to stabilize different conformational isomers of the parent compound. The minimal structural modifications of the conformationally flexible Gly10 residue, as substitutions for L‐Ala, D‐Ala, or Aib (replacing of hydrogen atoms by methyl groups), were applied to obtain octa‐ and hepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
18
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 22 publications
9
18
0
Order By: Relevance
“…Analog 3 (Ac‐Nle‐c[Asp‐Pro‐ D‐ Nal(2′)‐Arg‐ D ‐Nal(2′)‐Lys]‐NH 2 , PG‐928) which differs from 2 by having a D ‐Nal(2′) in position 7, was equipotent to 1 at all three receptors, and it also was equipotent as an antagonist at the h MC3R and the h MC4R when compared with SHU‐9119 as shown in Table 2. These results clearly confirm, similar to m MCRs previously reported (32), that the melanocortin receptor subtypes do not discriminate ligands with an indole or a naphthyl side chain at position 9. However, analog 4 , Ac‐Nle‐c[Asp‐Pro‐ D‐ Phe‐Arg‐D‐Phe‐Lys]‐NH 2 (PG‐929, Table 1) with a D ‐Phe in position 9 was less active as an agonist at all receptors, while 5 (Table 1, Ac‐Nle‐c[Asp‐Pro‐ D‐ Nal(2′)‐Arg‐ D‐ Phe‐Lys]‐NH 2 , PG‐930) retained substantial antagonist potency at the h MC3R and the h MC4R.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Analog 3 (Ac‐Nle‐c[Asp‐Pro‐ D‐ Nal(2′)‐Arg‐ D ‐Nal(2′)‐Lys]‐NH 2 , PG‐928) which differs from 2 by having a D ‐Nal(2′) in position 7, was equipotent to 1 at all three receptors, and it also was equipotent as an antagonist at the h MC3R and the h MC4R when compared with SHU‐9119 as shown in Table 2. These results clearly confirm, similar to m MCRs previously reported (32), that the melanocortin receptor subtypes do not discriminate ligands with an indole or a naphthyl side chain at position 9. However, analog 4 , Ac‐Nle‐c[Asp‐Pro‐ D‐ Phe‐Arg‐D‐Phe‐Lys]‐NH 2 (PG‐929, Table 1) with a D ‐Phe in position 9 was less active as an agonist at all receptors, while 5 (Table 1, Ac‐Nle‐c[Asp‐Pro‐ D‐ Nal(2′)‐Arg‐ D‐ Phe‐Lys]‐NH 2 , PG‐930) retained substantial antagonist potency at the h MC3R and the h MC4R.…”
Section: Resultssupporting
confidence: 92%
“…Gly 10 is the normal residue in position 10 of α ‐MSH, as is Lys 11 . We have previously shown that the addition of Gly 10 in some linear and cyclic peptides increases potency at melanotropin receptors (30–33). These results have been explained by possible differences in the mode of binding of these peptides at the receptors.…”
Section: Resultsmentioning
confidence: 99%
“…This side chain orientation may explain how peptide 1 possesses the amphiphilic characteristic similar to structures observed in other melanocortin ligands. 38,78,82 Peptide 12, containing a bulkier DNal(1′) residue instead of the DPhe amino acid, is a full agonist at mMC1R and mMC3- Tyr-c[ -Asp-His-DPhe-Arg-DNal(2′)-Asn-Ala-Phe-Dpr]-Tyr-NH2 6.50 0. 67 10 5Rs, albeit with 40-fold decreased potency at the mMC1 and 330-fold decreased agonist potency at the mMC3, as compared to peptide 1.…”
Section: H Nmr and Computer-assisted Molecular Modeling-based Structusupporting
confidence: 83%
“…The amphiphilic nature of the structure may be important for the geometry of binding of the molecule with its receptor because the hydrophobic portion can allow interaction with the cell membrane, and the charged portions can interact with the charged moieties on the actual receptor. As described earlier, the amphiphilic folds of the molecule are also observed in the simulations of Al‐Obeidi et al (53) and Nikiforovich et al (69) and the latter have proposed that the hydrophobic side chains in the message region may form a continuous hydrophobic surface that may interact with the receptor. The stacked nature of hydrophobic residues in the message regions observed in Family IV also creates hydrophobic surface but in this case it is much more compact than the one observed in the models of Nikiforovich et al The stacked nature of this rings was also proposed in NMR studies (51, 57, 61), and this enhanced compactness of the hydrophobic surface may be expected to preferred in an aqueous environment.…”
Section: Discussionsupporting
confidence: 60%
“…Conformations similar to the transduction state were reported by the same group for another type of superpotent analog, which had cyclization effected between the residues at 5 and 11 by introducing a pair of dibasic amino acid residues (66). More recent studies in that laboratory (69), using a large number of cyclic analogs of α‐MSH, have led to a hypothesis that the formation of a continuous hydrophobic surface by the aromatic moieties of His6, Phe7 and Trp9 may be characteristic of active ana‐logs and may be important for the interaction with the receptor.…”
Section: Discussionmentioning
confidence: 99%